Comprehensive Evaluation of Biomass Energy Technologies in China - Yang, Qing; Han, Fei; Wu, Xudong; Wang, Deyuan; Wang, Xianhua; Yang, Haiping; Zhang, Shihong; Chen, Hanping (Journal of Technology Innovations in Renewable Energy, 2014)
Based on a comprehensive review of the different biomass energy technologies in China, a hybrid evaluation model founding on Analytic Hierarchy Process (AHP) is proposed to offer a comprehensive evaluation of a variety of biomass energy technologies in China. In this model, three evaluation criteria, including the applicability of technology, economic viability and environment-friendly, are defined and nine indicators, including resources supply, equipment and technology, energy efficiency, energy grade, production cost, economic benefit, ecological impact, environmental pollution and social benefit, are devised. Priorities are established in this study based on pairwise comparisons of the elements. In addition, the model has been validated by various utilization technologies reported in literatures. Results show that environmental pollution, social benefit, ecological impact and resources supply greatly impact on the application of biomass technologies, followed by economic benefit. Besides, it is demonstrated that integrated technologies of biomass energy, which is closely related with residential daily life and compatible with local ecological environment, possess evident superiority. Furthermore, the outcome can be supportive for guiding future development of biomass energy in China.